Penurunan Debit Air Danau Dendam Tak Sudah untuk Irigasi Persawahan Setelah Perubahan Status Cagar Alam Menjadi Taman Wisata Alam - Pico Pudiansa; Rokky Gumanti; Muhammad Melian; Reflis, Reflis; Satria Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Dendam Tak Sudah is a lake located in the Bengkulu Province. It is situated in the Dusun Besar Village, Singaran Pati District, Bengkulu City, Bengkulu Province. The total area of Danau Dendam Tak Sudah is 559 hectares, with a surface area of 68 hectares. Since the issuance of Decree No. 79/MENLHK/SETJEN/PLA.2/1/2019 dated January 21, 2019, regarding the strengthening of the main function within the forest function of part of the DDB Nature Reserve area, it has been designated as a Nature Tourism Park in Bengkulu City, Bengkulu Province, covering an area of approximately 88 hectares. The status of the Danau Dendam Tak Sudah area, which was previously a Nature Reserve, has now changed to a Nature Tourism Park. The purpose of this study is to analyze and understand the impact of the downgrade of the status of part of the Danau Dendam Tak Sudah area, formerly a Nature Reserve, to a Nature Tourism Park on the water condition in Danau Dendam Tak Sudah and its relation to the reduction in water discharge for rice fields. The objective of this research is to provide solutions to the government's decision-making process, emphasizing the consideration of environmental aspects and the interests of farmers, in addition to promoting tourism in Bengkulu City.